Konstruksi Model Pengembangan Desa Wisata menuju Smart Eco-Tourism di Desa Paksebali, Klungkung, Bali - I W. Pantiyasa (Jurnal Kajian Bali (Journal of Bali Studies), 2019)
This article was aimed to formulate the construction of tourism village development model towards smart eco-tourism in Paksebali village, Kungkung regency, Bali. The methods of collecting data included observation, interview, documentation, and Focused Group Discussion. The data were analysed using qualitative method and SWOT analysis. The findings showed that the political will of the government in Klungkung regency and Paksebali village, as well as the participation of the local community had a great contribution to the development of the tourism village. The analysis of internal and external factors were used to formulate alternative development strategies that included conservation and revitalization of arts and culture, nature and environment conservation. Village tourism product development was conducted in a gradual and sustainable manner. Improvement of facilities and infrastructure, included HR Quality Improvement, Strengthening tourism village institutions, marketing systems, and increasing community participation.